2014
DOI: 10.5713/ajas.2013.13301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eucalyptus Crude Oils Supplementation on Rumen Fermentation, Microorganism and Nutrient Digestibility in Swamp Buffaloes

Abstract: This study was conducted to investigate the effects of eucalyptus (E. Camaldulensis) crude oils (EuO) supplementation on voluntary feed intake and rumen fermentation characteristics in swamp buffaloes. Four rumen fistulated swamp buffaloes, body weight (BW) of 420±15.0 kg, were randomly assigned according to a 2×2 factorial arrangement in a 4×4 Latin square design. The dietary treatments were untreated rice straw (RS) without EuO (T1) and with EuO (T2) supplementation, and 3% urea-treated rice straw (UTRS) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
32
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 43 publications
10
32
1
Order By: Relevance
“…14,15 Moreover, eucalyptus oil (EO) exhibits substantial antibacterial properties because it contains significant amounts of tannins, phenolics, flavonoids and volatile oils. 16 Thao et al 17 discussed the biological activities of the extracted oils, including their bacteriostatic, fungistatic and anti-inflammatory activity, as well as their capability to modify ruminal biogases fermentation by reducing CH 4 production and their anti-protozoal activity. For example, significant growth inhibition of Staphylococcus aureus, Candida albicans and Escherichia coli was reported by applying EO.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Moreover, eucalyptus oil (EO) exhibits substantial antibacterial properties because it contains significant amounts of tannins, phenolics, flavonoids and volatile oils. 16 Thao et al 17 discussed the biological activities of the extracted oils, including their bacteriostatic, fungistatic and anti-inflammatory activity, as well as their capability to modify ruminal biogases fermentation by reducing CH 4 production and their anti-protozoal activity. For example, significant growth inhibition of Staphylococcus aureus, Candida albicans and Escherichia coli was reported by applying EO.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to these results, the VFA concentrations were reduced by the inclusion of EUO at 0.66, 1.0, 1.33, and 1.66 µl/ml (Kumar et al 2009). Also, Thao et al (2014) reported that 2 ml of EUO per day administered to swamp buffaloes reduced the proportions of acetate and acetate to propionate ratio but increased propionate proportion. Like the previous EO, EUO also increased the concentrations of ammonia-N in our cultures.…”
Section: Discussionmentioning
confidence: 99%
“…World's half of livestock population are raised in tropics and there is imminent need to address methane production by them (Thao et al, 2014). The public concern in overcoming global warming potential of animal farming operations through feed have to be taken cared (Kaufmann, 2015).…”
Section: Ikrs and Environmental Responsibilitymentioning
confidence: 99%